2014
DOI: 10.1111/efp.12103
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellites for the cacao frosty pod rot pathogen, Moniliophthora roreri

Abstract: Summary Moniliophithora roreri, causal agent of cacao frosty pod rot, is considered one of the most devastating pathogens of this crop. In this study, we report the development of and validation of 28 microsatellite loci from an enriched library. From these, ten loci were demonstrated to be polymorphic in an Ecuadorian population composed of 27 isolates. The mean number of alleles per locus was 3.2, and the observed mean and expected heterozygosity were 0.03 and 0.43, respectively. The polymorphic microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The molecular marker analysis category was formed by papers that developed or used existing molecular markers to investigate pathogen genomes. Molecular markers for population studies were developed for M. perniciosa [ 53 , 63 , 64 ], M. roreri [ 46 , 65 ] and Phytophthora spp. [ 46 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular marker analysis category was formed by papers that developed or used existing molecular markers to investigate pathogen genomes. Molecular markers for population studies were developed for M. perniciosa [ 53 , 63 , 64 ], M. roreri [ 46 , 65 ] and Phytophthora spp. [ 46 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…These groups were split into two broader groups: Orientalis and Occidentalis. Using microsatellite markers, Melo et al (2014) observed limited Mr genetic diversity with 3.2 alleles per locus and a heterozygosity of 0.03 amongst Mr isolates from Ecuador. Single nucleotide polymorphism (SNP) marker analysis showed that Mr isolates collected from throughout its range could be placed into two major groups (groups a and b), and predicted the upper Magdalena Valley of Colombia as the centre of origin .…”
Section: Disease Cyclementioning
confidence: 96%
“…All relevant studies using molecular markers indicate that Mr propagates clonally (Ali et al ., ; Jaimes et al ., ; Melo et al ., ; Phillips‐Mora et al ., ). Yet, low genetic diversity was also observed in Mp , a species that undergoes meiosis, using microsatellite markers (2.9 alleles per locus and 0.15 heterozygosity) (Gramacho et al ., ; Silva et al ., ) and retrotransposon‐based markers (diversity of 0.06) (Santana et al ., ), and was attributed to homothallism.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…DNA was extracted from M. roreri mycelium grown for 11 days in a PDA [28]. Twelve primers were used, 10 from [29] (primers mr-6, mr-10, mr-11, mr-12, mr-13, mr-15, mr-22, mr-30, mr-31 and mr-33) and two from [23] (primers 816 and 890). The final reaction volume was 25 µL, containing the following mixture: 12.5 µL of Go Taq ® Green Master mix combined with 0.5 µL of each primer, 2 µL of DNA (30 ng/µL), and 9.5 µL of bi-distilled water.…”
Section: Dna Extraction and Amplification Of Simple Sequence Repeats ...mentioning
confidence: 99%